Catalysis of glycerol acetylation on solid acid catalyst: a review - Nur Hidayati; Rahmah Puspita Sari; Herry Purnama (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Biodiesel is a substitute fuel that is environmentally friendly, biodegradable, and sustainable. The need for biodiesel continues to increase. Biodiesel is made through the process of transesterification of triglycerides and alcohol. Glycerol is a side-effect of biodiesel products with a capacity of 10% of the total weight of its production. Glycerol is the simplest glyceride compound and has several functions as a primary ingredient in chemical production. Through acetylation, glycerol is converted to a material that has a higher sale value. Both homogeneous and heterogeneous catalysts are the acetylation approach to achieve the desired product, namely acetyl glycerol esters (mono-, di- and triacetin). However, in the process, the catalyst’s type and characteristics significantly affect the yield and conversion of the product and the deactivation or reusability of the catalyst, which can inhibit the catalyst’s utilization and effectiveness; therefore, it must be studied further. Besides, the parameters that affect the reaction will also be assessed.